Varietal performance of potato on induction and development of microtuber in response to sucrose - Md. Sadek Hossain; M. Mofazzal Hossain; Tofazzal Hossain; M. Moynul Haque; Mohammad Zakaria; Md. Dulal Sarkar (Annals of Agricultural Sciences, 2017)
Tissue culture techniques are the most momentous and extensively method to produce disease-free quality plantlets and microtubers in potato. In spite of this, there has been a lack of research information into in vitro microtuberization for seed tuber production program in Bangladesh. In this experiment, we assessed the appropriateness of different concentrations of sucrose with especial accent on their effects for induction and development of microtuber in potato varieties. In vitro plantlets of three potato varieties; Asterix, Granola, and Diamant were treated with eight level of sucrose as 0, 3, 4, 6, 8, 10, 12 and 14% for 70 days of incubation producing microtuber. Asterix induces microtuber after 10.69 days, it was statistically shorter duration than other two varieties. Tuberization did not occur without sucrose and were required a minimum (8.92 days) with 8% sucrose, while it delayed with either increasing or decreasing rate of sucrose concentration. A single number of microtuber was not formed in absence of sucrose after 28 days of incubation. Microtuber plantlet−1 was the highest more or less in all varieties at harvest with 8% sucrose concentration. Hundred percent of microtuber below 250 mg induced in 3% sucrose concentration and from then the microtuber grade induction decreased with the increase of sucrose concentration. >500 mg grade microtuber produced by Granola (47.95%) with 10% sucrose while Diamant produced 50.15% above 500 mg grade microtuber with 14% sucrose. It is also noticeable by Astrerix variety where >500 mg microtuber were produced about 46.95% with 8% sucrose.